Secrecy Capacity of Cooperative D2D Multi-relay Communication System with Multiple Protocols Based on Max-Min Relay Selection - Nurul Maulida Fitri; Yunida Yunida; Melinda Melinda; Nasaruddin Nasaruddin (Jurnal Rekayasa Elektrika, 2023)
The utilization of other devices as relays in cooperative device-to-device (D2D) communication systems does not fully guarantee the security of confidential information from being intentionally or unintentionally accessed by eavesdroppers. Therefore, the implementation of a method to enhance the security performance of information is highly necessary. This paper proposes the application of relay selection mechanisms in a communication system with three relay protocols: Amplify-and-Forward (AF), Decode-and-Forward (DF), and Quantize-and-Forward (QF). The research method employs a mathematical modeling approach and simulations. The simulation results demonstrate an improvement in the level of information security in cooperative D2D communication systems using the proposed method in multiple relay protocols. The relay selection method has been evaluated and compared based on the Secrecy Outage Probability (SOP), which is one of the parameters for information security in the communication system. The SOP achieved is smaller with the implementation of the Max-Min relay selection technique in multi-relay cooperative communication networks. Considering the presence or absence of eavesdroppers, the SOP of the DF relay is smaller compared to other protocols. The impact of distance on secrecy capacity also indicates that the DF protocol utilizing multiple relays achieves higher results compared to other protocols, and the increased usage of relays also affects the simulation outcomes.